Antithrombotic therapy in patients with cerebral microbleeds. Issue 1 (February 2017) - Wilson, Duncan; Werring, David J.
Abstract : Purpose of review: Cerebral microbleeds (CMBs) are a radiological marker of cerebral small vessel disease corresponding to small haemosiderin foci identified by blood-sensitive MRI. CMBs are common in older community populations, and in individuals with ischaemic stroke or transient ischaemic attack (TIA), and intracerebral haemorrhage (ICH). We summarize how CMBs might contribute to assessing the future risk of ischaemic stroke and ICH to inform antithrombotic (antiplatelet or anticoagulant) decisions. Recent findings: CMBs are a risk factor for future ischaemic stroke and ICH in all community and hospital populations studied. Following ischaemic stroke/TIA treated with antithrombotics, increasing CMB burden increases the risk of ICH more steeply than that of ischaemic stroke. In ICH populations the risk of recurrent ICH increases with CMB burden, and is highest in those with strictly lobar CMBs or other haemorrhagic findings (e.g. cortical superficial siderosis) suggesting cerebral amyloid angiopathy (CAA). Summary: In ischaemic stroke or patients with TIA less than five CMBs should not affect antithrombotic decisions, although with more than five CMBs the risks of future ICH and ischaemic stroke are finely balanced, and antithrombotics might cause net harm. In lobar ICH populations, a high burden of strictly lobar CMBs is associated with CAA and high ICH risk; antithrombotics should be avoided unless there is a compelling indication.